Brand Valuation of Garment Companies for Tax Purposes - Rahmat Heryat Furqon; Azhar Affandi; Jaja Suteja; Dadang Suwanda (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
Valuation of intangible assets is carried out to determine a certain value objectively and professionally in accordance with regulatory provisions for non-monetary assets with no identifiable or unidentifiable physical form (goodwill). Many intangible assets will not be recognized in the financial statements because they fail to meet the definition of an asset or the recognition criteria. The transfer of Intangible Assets often uses Book Value so that there is no tax obligation, the purpose of this study is to determine the Fair Market Value of Intangible Assets in the form of Brands for tax purposes with valuation that is to carry out financial statement analysis, macroeconomic analysis, industry analysis and application of Approaches and Methods Selected rating. The approach used is using the Income Approach with the Royalty Savings Method, the results of the valuation obtained the Fair Market Value of Brand X of Rp. 23,978,000,000; (Twenty Three Billion Nine Hundred Seventy Eight Million Rupiah).